Integrating the Tilawatil Qur'an Method into Extracurricular Activities Based on Local Wisdom and Sustainable Education: Integrasi Metode Tilawatil Al-Qur’an dalam Ekstrakurikuler Berbasis Kearifan Lokal dan Pendidikan Berkelanjutan - Ibrahim, Maulana Malik; Ahmad Ma'ruf (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
Background: This study aims to examine the integration of the Tilawatil Qur’an method in developing the correction (tashih) of Qur’anic recitation through extracurricular activities. The method emphasizes not only the melodic beauty of recitation but also the fluency and accuracy of pronunciation in accordance with tajwid rules. In the context of Islamic education, this activity plays a crucial role in shaping students’ religious character while improving the quality of their recitation. The integration is carried out by embedding local wisdom—such as culturally familiar recitation styles and community-based mentoring—into structured extracurricular programming, ensuring both contextual relevance and sustainability. Research Objectives: To examine how the Tilawatil Qur’an method can be integrated into extracurricular activities to improve students’ Qur’anic recitation correction (tashih). Methods: The study employs a qualitative approach with a case study method. Data were collected through direct observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data condensation, data display, and conclusion drawing. Conclusions: The findings show that the structured integration of the Tilawatil Qur’an method significantly enhances students’ recitation correction abilities. Despite challenges such as limited time, low student motivation, and teachers’ limited understanding of the method, the program continues to run effectively due to well-planned instructional strategies. This research fills a gap in Qur’anic pedagogy by examining extracurricular tashih practices in a structured framework, which have received limited attention in prior literature. This research contributes theoretically to the development of Qur’anic learning methods and practically to improving the quality of religiously oriented extracurricular activities, especially those rooted in local culture and designed for long-term sustainability. The novelty of this research lies in the integration of the Tilawatil Qur’an method with local wisdom and sustainability strategies within a structured extracurricular framework. These findings have practical implications for developing culturally rooted Qur’anic learning models that can be integrated into formal curricula or adopted as part of project-based learning initiatives within Islamic schools.